Unified gated basis modulation for agricultural virtual-to-real translation - Ruofei Ma; Xianglei Liu; Yi Zhang; Yuefeng Du; Lei Liu; Mingwei Du; Zhiqiang Guo (Computers and Electronics in Agriculture, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Application-dependent effects of tea waste biochar on PFAS mobility and N2O and CH4 emissions in agricultural soil - Liting Hao; Dongdong Zhang; Ziheng Zhao; Jun Wang; Ruofei Wang; Miao Li (Waste Management, 2026)

Graph-Regularized Point-to-Trajectory Association for RS-AIS fusion toward maritime moving-ship identification and spatial refinement - Xin Du; Ruofei Zhong; Marco Scaioni; Marco Gianinetto; Shiyue Zhang; Qingyang Li; Zhenxing Sun; Chengming Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Mechanisms of extreme rainfall partitioning in contour ridge system: A modified SCS-CN method incorporating microtopographic and ridge geometry effects - Juan An; Guohui Li; Ruofei Liu; Yuanzhi Wu; Xiyuan Wu; Rui Zhang; Yao Zhao (Soil and Tillage Research, 2026)

Alteration of individual morphological brain networks in preschool children with autism spectrum disorder - Weixuan Qin; Chunlan Sun; Shuang Ding; Ruofei Ma; Bin Qin; Kaiping Huang; Yun Zhang; Longlun Wang; Jinhua Cai (Brain Imaging and Behavior, 2026)

Low-barrier interface via noble metal induction for external energy-free ppb-level room-temperature formaldehyde sensing - Ziming Yang; Jiangnan Chang; Ying Qiao; Sitao Lv; Leqi Zhang; Yifei Fan; You Wu; Ruofei Lu; Hao Li; Yanan Guo; Patrick J. French; Jun Yin; et al. (Chemical Engineering Journal, 2026)

Integrated mangrove aquaculture systems enhance macrobenthic productivity: A case study in Zhanjiang, China - Haiping Huang; Yuanmin Sun; Kunxian Tang; Linjun Sun; Ruofei Zhang; Heyang Li; Yong Ma (Marine Pollution Bulletin, 2026)

Nano-biochar enhances energy taxis of Shewanella oneidensis MR-1 and the bio-utilization of minerals and Cr(VI) - Tianao Zhou; Min Li; Guangfei Liu; Huali Yu; Lecheng Liu; Ruofei Jin; Ziyi Zhang (Journal of Cleaner Production, 2026)

The research of a novelty bio-based flame retardant derived from the synthetic combination of alkaline-extracted polymer substances from wastewater sludge with phytic acid - Congcong Li; Ming Cheng; Ruiqin Chen; Ruofei Wang; Xiangyang Wang; Liang Zhao; Xiaodi Hao; Chen Shi; Wei Zhang (Journal of Environmental Management, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Particle size–dependent molecular perturbations induced by copper nanoparticles in marine medaka (Oryzias melastigma): an integrated miRNA–mRNA analysis - Pengrui Ren; Peipei Zhang; Jingyuan Shi; Hongbo Li; Ruofei Jin; Hongjun Li (Frontiers in Marine Science, 2026)
Introduction Copper nanoparticles (Cu-NPs) have been increasingly released into marine environments due to their extensive applications, posing potential risks to marine organisms and human health. Although Cu-NPs of different particle sizes exhibit distinct toxicities—largely attributed to variations in specific surface area and Cu 2+ dissolution rates—current physicochemical parameters still fail to fully explain these toxic effects, and the underlying molecular mechanisms remain unclear. Methods This study aimed to investigate the toxic effects and underlying molecular mechanisms of Cu-NPs of different nominal primary diameters (10 nm, 50 nm, and 100 nm) on the marine medaka ( Oryzias melastigma ). Results LC 50 point estimates suggested slightly higher toxicity for smaller Cu-NPs. Integrated miRNAomic and transcriptomic analyses revealed that Cu-NPs-10 exposure markedly activated multiple metabolic pathways, including drug metabolism–cytochrome P450, retinol metabolism, and ascorbate and aldarate metabolism. Cu-NPs-50 exposure primarily affected neurodevelopment and synaptic signaling, with predicted miRNA–mRNA associations including miR-202 with mprip-like and miR-2187 with adgrg2-like . In contrast, Cu-NPs-100 exposure activated inflammation- and barrier repair-related networks, with potential miRNA–mRNA relationships involving miR-202 with tm4sf5 , miR-106a, miR-132c, miR-200b, and miR-202 with znfx1 , as well as miR-2187 and miR-202 with rhbdl2 . Discussion Collectively, the integrated miRNA–mRNA analysis suggests that smaller Cu-NPs show a correlation with more intense molecular stress responses than larger particles under seawater transformations (e.g., aggregation/dissolution), and provides insights into the key regulatory networks potentially underlying these size-associated responses.

End-to-end 3D reconstruction of subway tunnel scenes via local feature aggregation - Yue Lu; Haili Sun; Zhenxin Zhang; Ruofei Zhong; Xiaoxu Ren; Mingze Sun (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

The impact of the Beijing winter olympics on green technology innovation: an analysis using the synthetic control method - Ruofei Lin; Junpei Huang; Zixuan Zhang (Environment, Development and Sustainability, 2025)

Research on the assembly and independent self-stress modes of one-dimension array tensegrity structures - Ruofei Li; Xingfei Yuan; Zhihong Zhang (Engineering Structures, 2025)

Scientometric insights into the human settlement environment in the karst regions: trends, challenges, and future directions - Xiaoqi Li; Ruofei Guan; Jiaojiao Zhu; Qichi Yang; Bin Zhang (Landscape and Ecological Engineering, 2025)

A 1DCNN-SENet-LSTM model for UGW-based automatic evaluation of grouting void location in post-tensioned concrete structure - Ruofei Liu; Longguan Zhang; Junfeng Jia; Shengli Li; He Guo; Binli Guo (Engineering Structures, 2025)

Microbial inoculants addition increases microbial necromass but decreases plant lignin contribution to soil organic carbon in rice paddies - Quanyi Hu; Xuelin Zhang; Ziwei Zhang; Ruofei Wang; Cheng Feng; Yingxin Xie; Shaojie Chen; Tianqi Liu (Soil and Tillage Research, 2025)

Encephalomyocarditis virus non-structural protein 2C induces the degradation of NDP52 autophagy protein to promote its own survival - Rongqian Mo; Rongrong Cheng; Pingan Dong; Tingting Ma; Yaxin Zhang; Jingying Xie; Shasha Li; Huixia Li; Adi Idris; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

Design, synthesis, bioactivity and action mechanism of N-substituted N′-phenylpicolinohydrazides against phytopathogenic fungi - Yuhao Zhang; Ruofei Bai; Tengyi Du; Yiwei Wang; Bohang Zhou; Congwei Zhou; Le Zhou (Molecular Diversity, 2025)

Extracellular vesicles engineered to directly target encephalomyocarditis virus ameliorates multi-organ viremia in a lethal infection model - Jiayu Yue; Yanmei Yang; Adi Idris; Wenjing Jin; Yaxin Zhang; Yongfang Chen; Xiangrong Li; Huixia Li; Shasha Li; Yanqiao Wen; Ruofei Feng; Jingying Xie (Veterinary Microbiology, 2025)

Design, bioactivity and mechanism of N′-phenyl pyridylcarbohydrazides with broad-spectrum antifungal activity - Yuhao Zhang; Bohang Zhou; Pengan Wei; Le Liu; Ruofei Bai; Yiwei Wang; Le Zhou (Molecular Diversity, 2025)

High dielectric sulfonyl-containing polyimide binders optimize the long-term stability and safety of NCM811 lithium-ion batteries at high voltages - Lin Chen; Dandan Yang; Junhao Xin; Xiaowei Zhou; Yuchen Zhang; Zixin Lv; Tiegen Guo; Qinghai Chen; Ruofei Gao; Ying Wang; Ning Wang; Shuanyan Kang; et al. (Chemical Engineering Journal, 2025)

Lattice strain engineering in ZnGa2O4 for selective CO2 photoreduction enhancement - Xian Shi; Jing Zhang; Ruofei Tang; Weidong Dai; Yangyang Yu; Xing’an Dong (Chemical Engineering Journal, 2025)

Online optimization of adjustable settings for agricultural machinery assisted by digital twin - Dafang Guo; Linze Wang; Yuefeng Du; Zhikang Wu; Weiran Zhang; Qiao Zhi; Ruofei Ma (Computers and Electronics in Agriculture, 2024)

LSANNet: A lightweight convolutional neural network for maize leaf disease identification - Fu Zhang; Ruofei Bao; Baoping Yan; Mengyao Wang; Yakun Zhang; Sanling Fu (Biosystems Engineering, 2024)

Remediation of arsenic- and nitrate-contaminated groundwater through iron-dependent autotrophic denitrifying culture - Jia-Bo Liu; Hongbin Zhang; Hefei Wang; Banghui He; Huixuan Wang; Ruofei Jin; Tian Tian (Environmental Research, 2024)

Eggshell powder as a bio-filler for starch and gelatin: Ternary biodegradable composite films manufactured by extrusion compression molding - Ting Li; Ruofei Li; Haodan Luo; Lu Peng; Jie Wang; Shasha Li; Man Zhou; Xiangyang Yuan; Zhiqing Zhang; Hejun Wu (Food Hydrocolloids, 2024)

What induced long-term Hg enrichment in interglacial sediments during the Cryogenian - Ruofei Yang; Haifeng Fan; Hui Zhang; Danish Khan; Hongjie Zhang; Xuewu Fu; Hanjie Wen (Precambrian Research, 2024)

Hg isotope evidence for oceanic oxygenation during the Cambrian Explosion - Haifeng Fan; Xuewu Fu; Ruofei Yang; Hanjie Wen; Chunlin Hu; Jack F. Ward; Hongjie Zhang; Hui Zhang; Xingliang Zhang (Geochimica et Cosmochimica Acta, 2023)

Biomimetic optimized concept with Murray networks for accelerated solar-driven water evaporation - Ruofei Zhu; Ke Li; Dan Wang; Jipeng Fei; Jun Yan Tan; Shuzhou Li; Jichao Zhang; Hong Li; Shaohai Fu (Chemical Engineering Journal, 2023)

Research on Coal Pillar Width and Support Design of Gob-Side Entry - Yong Yang; Jian Sun; Wei Wang; Ruofei Zhang (Geotechnical and Geological Engineering, 2023)

5300‐Year‐old soil carbon is less primed than young soil organic matter - Jiao Su; Haiyang Zhang; Xingguo Han; Ruofei Lv; Li Liu; Yong Jiang; Hui Li; Yakov Kuzyakov; Cunzheng Wei (Global Change Biology, 2023)
Soils harbor more than three times as much carbon (C) as the atmosphere, a large fraction of which (stable organic matter) serves as the most important global C reservoir due to its long residence time. Litter and root inputs bring fresh organic matter (FOM) into the soil and accelerate the turnover of stable C pools, and this phenomenon is termed the “priming effect” (PE). Compared with knowledge about labile soil C pools, very little is known about the vulnerability of stable C to priming. Using two soils that substantially differed in age (500 and 5300 years before present) and in the degree of chemical recalcitrance and physical protection of soil organic matter (SOM), we showed that leaf litter amendment primed 264% more organic C from the young SOM than from the old soil with very stable C. Hierarchical partitioning analysis confirmed that SOM stability, reflected mainly by available C and aggregate protection of SOM, is the most important predictor of leaf litter‐induced PE. The addition of complex FOM (i.e., leaf litter) caused a higher bacterial oligotroph/copiotroph ( K ‐/ r ‐strategists) ratio, leading to a PE that was 583% and 126% greater than when simple FOM (i.e., glucose) was added to the young and old soils, respectively. This implies that the PE intensity depends on the chemical similarity between the primer (here FOM) and SOM. Nitrogen (N) mining existed when N and simple FOM were added (i.e., Glucose+N), and N addition raised the leaf litter‐induced PE in the old soil that had low N availability, which was well explained by the microbial stoichiometry. In conclusion, the PE induced by FOM inputs strongly decreases with increasing SOM stability. However, the contribution of stable SOM to CO 2 efflux cannot be disregarded due to its huge pool size.

Alterations in functional network centrality in first-episode drug-naïve adolescent-onset schizophrenia - Ming Zhou; Lihua Zhuo; Ruofei Ji; Yingxue Gao; Hongchao Yao; Ruohan Feng; Lianqing Zhang; Guoping Huang; Xiaoqi Huang (Brain Imaging and Behavior, 2022)

Nanozymes: created by learning from nature - Ruofei Zhang; Kelong Fan; Xiyun Yan (Science China Life Sciences, 2020)

Petrogenesis and timing of emplacement of porphyritic monzonite, dolerite, and basalt associated with the Kuoerzhenkuola Au deposit, Western Junggar, NW China: implications for early Carboniferous tectonic setting and Cu–Au mineralization prospectivity - Feng Yuan; Yu-Feng Deng; Taofa Zhou; Dayu Zhang; Chao Xu; Simon M. Jowitt; Ruofei Zhang; Bingbing Zhao (International Geology Review, 2017)

National serosurvey of encephalomyocarditis virus in healthy people and pigs in China - Ruofei Feng; Jia Wei; Haixia Zhang; Jingjing Fan; Xiangrong Li; Dan Wang; Jingying Xie; Zilin Qiao; Mingsheng Li; Jialin Bai; Zhongren Ma (Archives of Virology, 2015)

A new hierarchical moving curve-fitting algorithm for filtering lidar data for automatic DTM generation - Wei Su; Zhongping Sun; Ruofei Zhong; Jianxi Huang; Menglin Li; Jingguo Zhu; Keshu Zhang; Honggan Wu; Dehai Zhu (International Journal of Remote Sensing, 2015)

Good response in a patient with deep-seated subcutaneous ulcer due to Candida species - Liyan Xi; Xiqing Li; Junmin Zhang; Changming Lu; Ting Xie; Ruofei Yin (Mycopathologia, 2007)